A Note on Leptobyrsa Decora Drake (Hemiptera: Tingitidae) - a Bio-control Agent of Lantana Camara (verbenaceae) - Misra, Ram Mohan (Indian Forester, 1985)
The paper outlines the procedure adopted during transportation of Leptobyrss decora Drake (Hemiptera: Tingitidae) from Bombay to Dehra Dun by train along with its life-history studies under Dehra Dun conditions. The bug oviposits 83 eggs on the mid-rib or main vein of mature leaves of Lantana. Incubation period ranges from 12-14 days. Nymphal period recorded was 22 days. Life cycle is completed in 38 days. Adult live 12-14 weeks.